Copro-molecular identification of intestinal nematode infections in a rural community in East Malaysia. (February 2021) - Hassan, Nur-Amirah; Thodsapol, Autchariya; Lim, Yvonne Ai Lian; Wan Sulaiman, Wan Yusoff; Sidi Omar, Siti Farah Norasyikeen; Umsakul, Kamontam; Ngui, Romano
Abstract: Soil-transmitted helminth (STH) infections are the most common intestinal parasitic infections of medical importance in humans. The infections are widely distributed throughout tropical and subtropical countries, particularly among disadvantaged and underprivileged communities. In Malaysia, STH infections is highly prevalent, especially among the indigenous groups. However, species identification through molecular studies is still lacking. Using molecular techniques, this study was conducted to identify STH species that infect humans. Faecal samples were collected from three Iban tribal longhouses in the rural area of Sarikei Division, Sarawak. Positive faecal samples by microscopy were subjected to PCR and sequenced for species identification. Based on the microscopy examination, the most prevalent STH infection was Ascaris, followed by hookworm and Trichuris . All microscopy-positive samples were then PCR-amplified. The amplicons were sequenced, aligned, and compared with other sequences in the GenBank database. The results showed that Ascaris lumbricoides was the predominant STH species, followed by Trichuris trichiura, Ancylostoma duodenale, and Necator americanus . Our findings were contradictory to past studies, as we showed that A. duodenale was more abundant than N. americanus . Socioeconomic improvement and health education programs should be included in the management and prevention of public health strategies against STH.